2012 IEEE RO-MAN: The 21st IEEE International Symposium on Robot and Human Interactive Communication 2012
DOI: 10.1109/roman.2012.6343844
|View full text |Cite
|
Sign up to set email alerts
|

Sharing effort in planning human-robot handover tasks

Abstract: For a versatile human-assisting mobilemanipulating robot such as the PR2, handing over objects to humans in possibly cluttered workspaces is a key capability. In this paper we investigate the motion planning of handovers while accounting for the human mobility. We treat the human motion as part of the planning problem thus enabling to find broader type of handing strategies. We formalize the problem and propose an algorithmic solution taking into account the HRI constraints induced by the human receiver presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…(Sisbot et al, 2005) proposed a navigation planner that creates safe, legible, and socially acceptable paths for approaching a person for a handover. As a progression from this work, the motion planner was extended to account for the amount of human motion required to handover, allowing the robot to choose the best handover location based on context (Mainprice, Gharbi, Simeon, & Alami, 2012). …”
Section: Handover Behaviors For Robotsmentioning
confidence: 99%
“…(Sisbot et al, 2005) proposed a navigation planner that creates safe, legible, and socially acceptable paths for approaching a person for a handover. As a progression from this work, the motion planner was extended to account for the amount of human motion required to handover, allowing the robot to choose the best handover location based on context (Mainprice, Gharbi, Simeon, & Alami, 2012). …”
Section: Handover Behaviors For Robotsmentioning
confidence: 99%
“…[6,26,31]) in human-robot interaction (HRI) have investigated how a robot should approach a human to initiate a handover. Basili et al [6] investigated how a human giver holds an object and approaches a human receiver in order to hand over the object, and indicated that their findings are transferable to a robot giver.…”
Section: Robot-to-human Handovermentioning
confidence: 99%
“…We consider variants of feature functions that have been introduced in previous work to account for human-robot interaction constraints [27], [28], [5]. We use two types of features inspired by the proxemics theory [29] and experiments in neuroscience [1].…”
Section: Feature Functionsmentioning
confidence: 99%